Nutrition care of cancer patients—A survey among physicians and nurses. (16th May 2018) - Erickson, N.; Paradies, K.; Buchholz, D.; Huebner, J.
Abstract : In order to quantify gaps in the provision of medical nutrition care in Germany and pinpoint specific areas of need, we collected data from patients, nurses and physicians. The results from the patient survey were published separately. A total of 506 participants from 69 certified centers answered the questions developed in cooperation with representatives from different professional groups (physicians, nurses and dietitians). Only about a third of participants reported that their institution provides structured pathways to nutritional counseling. 70.1% of those physicians reported that there was a specialist in nutrition available at their center while only 55.8% of nurses agreed. Only a quarter (24.2% and 26.9%) of physicians and nurses reported that their institution provided continuation of nutrition care after dismissal. A gap exists between need and consistent delivery of nutrition care services. Structured nutrition care pathways provided by legally certified nutrition professionals pathways are lacking. Cancer organizations may support this process by requiring documented nutrition care pathways and provision of services on a need based system into guidelines and certification criteria.